SURVIVAL AND INSECTS PESTS OF FOREST AND FRUITS SPECIES IN PUERTO ALMENDRA, LORETO REGION, PERU - PACHECO GÓMEZ, Tedi (2022)
Survival and insect pests of forest and fruit species in Puerto Almendra, Loreto, Peru were evaluated. Seedlings and cuttings of 15 forest species and 04 fruit species were obtained from natural populations and home gardens; these were installed in plots of 25 x 25 m, 25 individuals per species. Spondias purpurea cuttings had the highest survival (84%), Spondias mombin and Spondias dulcis reached 36% and 24% respectively. Plants from botanical seeds with Very good survival (80‑100%) were Copaifera paupera, Dipteryx odorata, Carapa guianensis, Swietenia macrophylla, Hura crepitans, Chorisia integrifolia, S. mombin, Guazuma ulmifolia, Pleurothyrium parviflorum and Amburana cearensis. With Good survival (60‑79%) are Cedrelinga cateniformis, Cedrela odorata, Genipa americana. In the category Regular (40‑59%) are Caryodendron orinocense y Calycophyllum spruceanum. In the category Bad (< 40%) are Calophyllum brasiliense and Aniba rosaeodora. Insect damage on plants was thoroughly checked, 04 pests were recorded: Hypsipyla grandella on S. macrophylla, C. odorata, and G. ulmifolia with incidences between 100 and 84%; Parasaissetia nigra had incidence (88%) on G. ulmifolia; Apioscelis bulbosa was found on G. ulmifolia, C. integrifolia, S. purpurea and S. dulcis with incidences of 80, 56, 8 and 4%, respectively and Aphis gossypii was recorded on S. purpurea with 20% incidence. This research provides information oriented to the propagation, management, and conservation of forest and fruit species in the Peruvian Amazon.